The influence of urbanization on the natural course of water in the Ouro Verde neighbourhood in Açailândia, Maranhão, Brazil (Research, Society and Development, 2023)
The natural hydrological cycle is composed of different processes with the course of rainwater defined by nature, and when humans become part of this system, they produce changes that negatively modify this cycle and generate significant impacts that are directly linked to the water cycle, and thus cause damage and losses to the population, generating floods, modifying the surface and subsurface runoff, which may trigger or increase erosion and silting of urban rivers, Therefore, the purpose of this study is to understand what these changes cause in the hydrological cycle, through soil sealing due to urbanization, and the influence of surface runoff due to runoff leading to an increase in rainfall flow influenced by soil permeabilization, through comparative means studying the flow of rainwater in a current and future context, surface runoff, estimating a possible urbanization in the region located upstream of the Ouro Verde neighborhood in Açailândia-MA.